Assessing nitrous oxide emissions and productivity of cropping systems for biogas production using digestate and mineral fertilisation in a coastal marsh site - Herrmann, Antje; Verma, Supriya; Techow, Anna; Kluß, Christof; Dittert, Klaus; Quakernack, Robert; Pacholski, Andreas; Kage, Henning; Taube, Friedhelm (Frontiers in Environmental Science, 2023)
Significant greenhouse gas emissions during substrate cultivation reduces the potential environmental benefits of biogas production. This study investigates the productivity of different cropping systems and their environmental impact in terms of nitrous oxide (N2O) emissions under the environmental conditions of the coastal marsh regions (Northern Germany) with heavy clay soils, in a two-year field trial (April 2009-March 2011). Treatments included four cropping systems (perennial ryegrass (Lolium perenne, PR) ley, continuous maize (Zea mays), a rotation (CR1) of spring wheat (Triticum aestivum), Italian ryegrass (Lolium multiflorum, IR) and maize, and a rotation (CR2) of maize, winter wheat and IR; two sources of N (nitrogen) fertilizers (calcium ammonium nitrate, and biogas residue (BR)), and three levels of N fertilizer applications (control, moderate, high). Nitrous oxide emissions were determined for the unfertilized and highly fertilized cropping systems comprising PR ley, CR1 and CR2. Cumulative annual N2O emissions varied across the treatments, ranging from 0.82 to 3.4 kg N2O-N ha-1 year-1. Under high N fertilizer applications, PR ley incurred higher N2O-N losses compared to other tested cropping systems, and IR cover crop caused relatively high N2O-N emissions in a short vegetation period. The study observed wide range of yield-scaled emissions (0.00-5.60 kg N2O-N (Mg DM)-1) for different crops, emphasizing the variability in N2O emissions linked to cropping systems. The N2O-N emission factors for the three cropping systems were found to be low to moderate for all treatments, ranging from 0.03 to 0.53% compared to IPCC default Tier 1 N2O-N EFs. The lower emissions in the study were associated with prolonged high soil moisture conditions (water filled pore space > 70%.), indicated by its negative correlation with N2O-N fluxes. Low dry matter and N yield of PR and of the wheat-IR sequence after BR application compared to other crops indicated a low N use efficiency. The estimation of N2O-N emissions based on N surplus was not promising specifically for the coastal study site where high groundwater level and organic matter in the soils were the predominant drivers for N2O-N emissions.